LKB1 coordinates neurite remodeling to drive synapse layer emergence in the outer retina - Burger, Courtney A; Alevy, Jonathan; Casasent, Anna K; Jiang, Danye; Albrecht, Nicholas E; Liang, Justine H; Hirano, Arlene A; Brecha, Nicholas C; Samuel, Melanie A (eLife, 2020)
Structural changes in pre and postsynaptic neurons that accompany synapse formation often temporally and spatially overlap. Thus, it has been difficult to resolve which processes drive patterned connectivity. To overcome this, we use the laminated outer murine retina. We identify the serine/threonine kinase LKB1 as a key driver of synapse layer emergence. The absence of LKB1 in the retina caused a marked mislocalization and delay in synapse layer formation. In parallel, LKB1 modulated postsynaptic horizontal cell refinement and presynaptic photoreceptor axon growth. Mislocalized horizontal cell processes contacted aberrant cone axons in LKB1 mutants. These defects coincided with altered synapse protein organization, and horizontal cell neurites were misdirected to ectopic synapse protein regions. Together, these data suggest that LKB1 instructs the timing and location of connectivity in the outer retina via coordinate regulation of pre and postsynaptic neuron structure and the localization of synapse-associated proteins.
Keywords: retina; synapse; axon; neuron; RIBEYE; VGLUT1